Using blog‐like documents to investigate software practice: Benefits, challenges, and research directions. Issue 11 (29th August 2019) - Rainer, Austen; Williams, Ashley
Abstract: Background An emerging body of research is using grey literature to investigate software practice. One frequently occurring type of grey literature is the blog post. Whilst there are prospective benefits to using grey literature and blog posts to investigate software practice, there are also concerns about the quality of such material. Objectives To identify and describe the benefits and challenges to using blog‐like content to investigate software practice, and to scope directions for further research. Methods We conduct a review of previous research, mainly within software engineering, to identify benefits, challenges, and directions and use that review to complement our experiences of using blog posts in research. Results and Conclusion We identify and organise benefits and challenges of using blog‐like documents in software engineering research. We develop a definition of the type of blog‐like document that should be of (more) value to software engineering researchers. We identify and scope several directions in which to progress research into and with blog‐like documents. We discuss similarities and differences in secondary and primary studies that use blog‐like documents and similarities and differences between the use of blog‐like documents and the use of already established research methods, eg, interview and survey.